Intrathyroidal Ectopic Thymus and Sonoelastographic Findings - Guneyli, Serkan; Aygun, Murat S.; Taskin, Orhun Cig; Sagtas, Ergin; Colakoglu, Bulent (Current Medical Imaging, 2021)
Background: Intrathyroidal ectopic thymus (IET) can be misdiagnosed as thyroid nodules. Purpose: The purpose of this study is to evaluate the sonoelastographic findings of IET in pediatric population. Methods: Twelve children who had been examined with ultrasound (US) and strain elastography between December 2012 and December 2019 were included in this retrospective study. The patients’ demographics and ultrasonographic findings, including the location, margin, shape, diameters, volume, structure, vascularity, and elastography values of the lesions were evaluated. Results: Twelve lesions were detected in 12 asymptomatic patients (3 females and 9 males) with a mean age of 4.67 ± 2.27 years. The most common location of the IET was in posterior part and middle third of thyroid, and the most common appearance on US was a well-defined, ovoid-shaped, and predominantly hypoechoic solid lesion with punctate/linear branching hyperechogenities. The lesions were mostly hypovascular on Doppler US. The mean strain ratio on elastography was found to be 1.10 ± 0.04. In the follow-up of 7 patients with available information, there was no significant change in size or appearance of IET on US. Conclusion: IET should be considered in the differential diagnosis of the lesions within the thyroid. The first step to accurately diagnose an IET is to consider it in the differential diagnosis. In addition to US, strain elastography findings can be used to distinguish IETs from papillary thyroid cancers which can have similar US appearance, and help avoid unnecessary biopsies.
Keywords: thymus